CASL for ASF+SDF Users - Mosses, Peter D. (BRICS Report Series, 1997)
Casl is an expressive language for the algebraic specification of software requirements, design, and architecture. It has been developed by an open collaborative effort called CoFI (Common Framework Initiative for algebraic specification and development). Casl combines the best features of many previous algebraic specification languages, and it is hoped that it may provide a focus for future research and development in the use of algebraic techniques, as well being attractive for industrial use. This paper presents Casl for users of the Asf+Sdf framework. It shows how familiar constructs of Asf+Sdf may be written in Casl, and considers some problems that may arise when translating specifications from Asf+Sdf to Casl. It then explains and motivates various Casl constructs that cannot be expressed directly in Asf+Sdf. Finally, it discusses the role that the Asf+Sdf system might play in connection with tool support for Casl.